The Influence of School Principal Leadership, Work Environment, and Work Discipline on Teacher Performance at Yapparindo Klungkung Tourism Vocational School - I Ketut Mandia; Tongam Sirait (PT. Publikasiku Academic Solution, 2024)
This research aims to identify the influence of school principal leadership, work environment, and work discipline on teacher performance at Yapparindo Tourism Vocational School. The research method used is quantitative with a multiple linear regression approach. The population in this study consists of all teachers at Yapparindo Tourism Vocational School, while the sample includes 56 teachers. The results of the regression analysis indicate that simultaneously, the three independent variables (school principal leadership, work environment, and work discipline) significantly affect teacher performance. However, partially, only the work discipline variable has a significant effect on teacher performance. Although the school principal leadership and work environment variables are not statistically significant, they remain important as both play a crucial role in creating a conducive work atmosphere. The coefficient of determination (R-square) obtained shows that the constructed regression model can only explain a small portion of the variation in teacher performance. This indicates that there are still other factors not covered in this study that also influence teacher performance. Based on the research findings, it is recommended that Yapparindo Tourism Vocational School focus more on improving teachers' work discipline. Additionally, the school needs to continually strive to enhance the quality of school principal leadership and improve working conditions. For future research, it is suggested to examine other factors that may affect teacher performance, such as work motivation, workload, and support from colleagues.